Experimental and non-experimental evidence on limited attention and present bias at the gym - Paul Muller; Wolfgang Habla (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2018)
We show that limited attention and present bias contribute to low levels of exercise. First, in a large randomized experiment, we find that email reminders increase gym visits by 13 % and that they benefit nearly all types of individuals. Limited attention can explain these effects. Second, using a novel dataset, we find that many bookings for gym classes are canceled, and that bookings are made even for classes that never have a waiting list. Comparing these findings to the predictions of a dynamic discrete choice model, we conclude that many gym members use bookings to commit themselves to future attendance.
Keywords: C93; D91; I12; 330; health behavior; randomized experiment; reminders; nudging; habit formation; limited attention; time inconsistency